Field-Induced Agglomerations of Polyethylene-Glycol-Functionalized Nanoclusters: Rheological Behaviour and Optical Microscopy - Sandor I. Bernad; Vlad Socoliuc; Izabell Craciunescu; Rodica Turcu; Elena S. Bernad (MDPI AG, 2023)
This research aims to investigate the agglomeration processes of magnetoresponsive functionalized nanocluster suspensions in a magnetic field, as well as how these structures impact the behaviour of these suspensions in biomedical applications. The synthesis, shape, colloidal stability, and magnetic characteristics of PEG-functionalized nanoclusters are described in this paper. Experiments using TEM, XPS, dynamic light scattering (DLS), VSM, and optical microscopy were performed to study chain-like agglomeration production and its influence on colloidal behaviour in physiologically relevant suspensions. The applied magnetic field aligns the magnetic moments of the nanoclusters. It provides an attraction between neighbouring particles, resulting in the formation of chains, linear aggregates, or agglomerates of clusters aligned along the applied field direction. Optical microscopy has been used to observe the creation of these aligned linear formations. The design of chain-like structures can cause considerable changes in the characteristics of ferrofluids, ranging from rheological differences to colloidal stability changes.